2000
DOI: 10.1177/095632020001100304
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Anti-HIV-1 Activity of sn-2-Substituted 1-O-Octadecyl-sn-Glycero-3-Phosphonoformate Analogues and Synergy with Zidovudine

Abstract: . Alkyl substitutions of one to four carbons at the sn-2 position of glycerol showed optimal antiviral activity. Both alkyl ether lipid analogues were strongly synergistic with zidovudine over a wide range of drug ratios and concentrations. 1-Ooctadecyl-sn-glycerol analogues of PFA have selective antiviral properties and warrant further evaluation as potential antiretroviral drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…This discrepancy is probably due to the limited ability of foscarnet to penetrate into cells, so that high concentrations of extracellular foscarnet are needed to reach inhibitory levels intracellularly. The permeability barrier can be circumvented by the use of alkylglycerol-conjugated derivatives of foscarnet, which are 10-to 35-fold more potent inhibitors of HIV-1 replication than is free foscarnet because they readily penetrate into cells and are then cleaved to form free intracellular foscarnet (13)(14)(15)21). These findings probably explain the differences in foscarnet sensitivity between our cell-based and enzyme assays.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This discrepancy is probably due to the limited ability of foscarnet to penetrate into cells, so that high concentrations of extracellular foscarnet are needed to reach inhibitory levels intracellularly. The permeability barrier can be circumvented by the use of alkylglycerol-conjugated derivatives of foscarnet, which are 10-to 35-fold more potent inhibitors of HIV-1 replication than is free foscarnet because they readily penetrate into cells and are then cleaved to form free intracellular foscarnet (13)(14)(15)21). These findings probably explain the differences in foscarnet sensitivity between our cell-based and enzyme assays.…”
Section: Resultsmentioning
confidence: 94%
“…W88G, E89K, L92I, S156A, and Q161L/H208Y were obtained by serial passage of HIV in MT-2 cells in the presence of escalating concentrations of foscarnet (13,31,52). Alkyglycerol conjugates of foscarnet have been developed to improve cellular uptake and reduce toxicity (14,15,21). Serial passage of HIV-1 in the presence of these conjugated forms of foscarnet yielded additional mutations including S117T, F160Y, and M164I (usually in combination with the L214F mutation) (13), which also conferred resistance to unconjugated foscarnet in virus culture assays.…”
mentioning
confidence: 99%
“…In the present study, we have obtained several lines of additional evidence that support our prior findings that the prodrugs are cleaved intracellularly to yield free and active PFA. First, we have shown that the PFA prodrugs inhibit HIV-1 in vitro (13). Second, the prodrugs have activity profiles against a panel of drug-resistant mutants similar to that of unmodified PFA.…”
Section: Discussionmentioning
confidence: 93%
“…1) are potent inhibitors of wild-type HIV-1 LAI . The IC 50 s for B-PFA, MB-PFA, and EB-PFA against HIV-1 LAI are 1.40, 0.28, and 0.39 M, respectively (13). In the present study, we evaluated the activities of these three analogs against a panel of NRTIresistant HIV-1 variants.…”
Section: Activities Of Pfa Prodrugs Against Nrti-resistant Hiv-1mentioning
confidence: 97%
See 1 more Smart Citation